Successful antibiotic treatment of Helicobacter pylori negative gastric mucosa associated lymphoid tissue lymphomas. Issue 5 (18th November 2005) - Raderer, M; Streubel, B; Wöhrer, S; Häfner, M; Chott, A
Abstract : Background and aims: The role of antibiotic treatment in early stage gastric mucosa associated lymphoid tissue (MALT) lymphoma not associated with Helicobacter pylori infection has not been investigated. Patients and methods: Six patients with localised gastric MALT lymphoma underwent antibiotic treatment with clarithromycin, metronidazole, and pantoprazole. Staging, including endosonography plus gastroscopy, computed tomography of the thorax and abdomen, colonoscopy, magnetic resonance imaging of the salivary glands, and bone marrow biopsy were performed to rule out distant spread of the disease. In addition, MALT specific genetic changes, including reverse transcriptase-polymerase chain reaction for t(11;18)(q21;q21), were tested in all patients. H pylori infection was ruled out by histology, urease breath test, serology, and stool antigen testing. Results: All six patients had MALT lymphoma restricted to the stomach, and no evidence of infection with H pylori was found. Only one patient tested positive for t(11;18)(q21;q21) while the remaining five displayed no genetic aberrations. Following antibiotic treatment, endoscopic controls were performed every three months. Five patients responded with lymphoma regression between three and nine months following antibiotic treatment (one partial remission and four complete responses). One patient had stable disease for 12 months and was then referred for chemotherapy. Conclusions: Patients with early stage gastric MALT lymphoma negative for H pylori might still benefit from antibiotic treatment as the sole treatment modality.